A Signal Integrity Based Rate Adaptation Algorithm - Seerangarajan, Mohan Kumar (International Journal of Computer Sciences and Engineering, 2025)
Wireless systems have gained momentum in recent years due to ease, universality and cost reduction. In a wireless network the signal degradation is time variant based on environmental factors. As variations in signal quality and interference from external sources affect the network, it is necessary and important to adapt the rate to the channel conditions via a rate adaptation algorithm driven by changes in the signal quality. This research addresses signal integrity in a local area network and proposes a rate adaptation algorithm for 802.11 wireless networks based on signal quality and packet error rate. The relationship between signal strength and packet error rate is analyzed and a new rate adaptation algorithm for 802.11n is presented. The algorithm developed in this thesis effectively adapts the rate to minimize packet error rate while it maximizes throughput. Through experiments, it has been shown that the proposed algorithm achieves better throughput compared to state of the technology rate adaptation algorithms currently implemented in commercial 802.11n systems